Effect of growth media and optical density on biofilm formation by Staphylococcus epidermidis - Mohd Hilmi, Abu Bakar; Mohammad Abdulraheem, AL-kafaween; Rao Sanaullah, Khan (2019)
Objective: The purpose of the present study was to assess the effects of media, optical density, and incubation time on biofilm formation by Staphylococcus epidermidis. Methods: The main procedure involved was fixing the bacterial film with 95% ethanol, staining with 0.1% crystal violet, releasing the bound dye with 33% glacial acetic acid, and measuring the optical density (OD) of the solution at 590 nm by using a microplate reader. Results: It was found that 3 and 5 days of incubation are critical for biofilm formation as indicated by the OD values of 0.55 - 0.06 and 0.70 - 0.39 in MHB and TSB respectively at OD 0.05. Similar results were noted for OD 0.1 in both media MHB and TSB while TSB showing slightly better results for biofilm formation. Conclusion: It is concluded that three days (72 hours) are required for obtaining effective biofilm formation in both MHB and TSB at 370C at OD 0.05 and OD 0.1.